PEDOT:PSS:sulfonium salt composite hole injection layers for efficient organic light emitting diodes - RASHID MOHD YUSOFF (Organic Electronics, 2021)
In this work, we propose a simple and effective approach to modify the optoelectronic properties of the commonly used poly(3,4-ethylenedioxylthiophene):poly(styrene sulfonate) (PEDOT:PSS) and consequently to improve hole injection and transport in organic light emitting diodes (OLEDs) using emissive layers based on a fluorescence copolymer. In particular, two triphenylsulfonium (TPS) salts that consist of the same TPS cation and two different counter anions, in particular, hexafluoroantimonate (SbF6) and trifluoromethane sulfonate (Triflate) were added in the PEDOT:PSS solution in various concentrations and the composite films were fully characterized for surface and optoelectronic properties and subsequently we employed as hole injection layers (HILs) in OLEDs. It is demonstrated that both, the counter anion and the concentration of TPS-salts in the PEDOT:PSS matrix play significant role in the optoelectronic properties of the composite and thus in the device performance. Although all TPS-salt modified PEDOT:PSS films exhibited higher work function (WF) values relative to the undoped one thus resulting in more efficient hole injection than pristine PEDOT:PSS, the PEDOT:PSS:TPS-Triflate with the lower concentration (10:1 v/v) showed the highest luminous (LE) and power efficiency (PE) values of 27.04 cd A−1 and 6.26 lm W−1, respectively. This extraordinary performance was ascribed to a significant increase in the conductivity of the composite film combined with the formation of an interface exciplex between the TPS-Triflate (acceptor) and the emissive copolymer (donor). This interfacial electroplex strongly confines the generated excitons and prevents their diffusion towards aluminum cathode which acts as exciton quencher.